Oral rehydration solution for maintenance therapy m severe acute gastroenteritis - Bambang Sugeng,, Bambang Sugeng, (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
Diarrheal disease is one of the main child health problems in Indonesia. Oral Rehydration Solution (ORS) is successfully used in rehydration therapy of mild and moderate dehydration due to acute gastroenteritis. Ringer lactate and ORS are distributed to primary health centres; however, Dextrose Saline or Dextrose 1/2 Saline are not. So far, maintenance therapy in Dr. Sardjito Hospital is done with Dextrose 1/4 Saline or Dextilise 1/2 Saline. The efficacy of maintenance therapy with ORS had been studied from the end of January through August, 1983. Fifiy-seven children suffering from severe dehydration due to acute gastroenteritis were admitted, comprising 29 children as study group and 28 children for control; but 5 children of the study group were excluded because of technical faults. Rehydration therapy was performed with 100 ml/kgBW Ringer lactate-5% glucose together with ORS during 4 hours (50 ml/kgBW during 1 hour and 50 ml/kgBW during the next 3 hours). For the maintenance therapy breast milk or diluted formula and ORS were given. DextroseÃ¢â¬â Saline or Dextrose - 1/2 Saline were used for maintenance therapy of the control group. The result of the maintenance therapy in the study group after 24 hours was one case moderate dehydration, 7 cases mild dehydration and 16 cases were rehydrated, whereas in the control group 13 cases mild dehydration and 15 cases were rehydrated. The difference was statistically not significant (p > 0,05). In this study no dehydration was obtained in the following days. It can be concluded that maintenance therapy with ORS on children suffering from severe dehydration due to acute gastroenteritis was succesful after intravenous rehydration with 100 ml/ kgBW solution during 4 hours. Key Words: rehydration - oral rehydration solution - breast milk - diluted formula - diarrhea